Critical questions: Advancing the health of female Veterans. Issue 10 (21st July 2017) - Muirhead, Lisa; Hall, Priscilla; Jones‐Taylor, Cedrella; Clifford, Gari D.; Felton‐Williams, Tasha; Williams, Kathy
Abstract: Purpose: Women are the fastest growing Veteran population in the United States and many receive all or part of their health care outside of the Department of Veterans Affairs (VA). The purpose of this article is to review the healthcare issues of women Veterans and discuss implications for care. Data sources: Review of selected literature, VA resources and guidelines, and expert opinion. Conclusions: Few providers are aware of the impact military service has on the health of women and fail to ask the all‐important question, "Have you served in the military?" Recognizing women's military service can reveal important information that can answer perplexing clinical questions, aid in designing comprehensive plans of care, and enable women to receive the assistance needed to address complex physical and psychosocial issues to improve the quality of their lives. Implications for practice: There are gender disparities related to physical health conditions, mental health issues, environmental exposures, and socioeconomic factors that contribute to female Veterans' vulnerabilities. Many of the health conditions, if recognized in a timely manner, can be ameliorated and shift the health trajectory of this population. Clinicians play a critical role in identifying health risk and helping female Veterans start the sometimes arduous journey toward wellness. Discovering and acknowledging women's military history is critical in ensuring quality care and appropriate decision making.